To prove:
sin A(1 + tan A) + cos A(1 + cot A) = sec A + cosec A
Solving L.H.S. of the equation :
⇒sin A(1 + tan A) + cos A(1 + cot A)⇒sin A + sin A tan A + cos A + cos A cot A⇒sin A + cos A+sin A×cos Asin A+cos A×sin Acos A⇒sin A + cos A+cos Asin2A+sin Acos2A⇒sin A + cos A+sin A cos Asin3A+cos3A⇒sin A + cos A+sin A cos A(sin A + cos A)(sin2A+cos2A−sin A cos A)⇒(sin A + cos A)(1+sin A cos Asin2A+cos2A−sin A cos A)⇒(sin A + cos A)(1+sin A cos A1−sin A cos A)⇒(sin A + cos A)(sin A cos Asin A cos A+1−sin A cos A)⇒(sin A + cos A)×sin A cos A1⇒sin A cos Asin A + cos A⇒sin A cos Asin A+sin A cos Acos A⇒cos A1+sin A1⇒sec A + cosec A.
Since, L.H.S. = R.H.S.
Hence, proved that sin A(1 + tan A) + cos A(1 + cot A) = sec A + cosec A.